Determinants of Using Digital Payments in Paying Zakat, Infaq, Sadaqah (ZIS) - Sapitri, Laili; Kafabih, An'im (SMART Insight, 2024)
Indonesia is a country with 87,02 % Muslim population. However, the realization of ZIS funds collected only reached 5.6%. Therefore, enhancing the utilization of digital payments is one of the ways BAZ and LAZ are focusing to increase ZIS fund collection. Theoretically, consumer choice theory, combined with Islamic perspective suggests that perceived income can be determinan factor people to pay ZIS digitally. Furthermore, Unified Theory of Acceptance and Use of Technology (UTAUT) also be used to determine paying ZIS digitally. The number of samples in this research was 210 which was obtained through purposive sampling using questionnaire as a tool for collecting primary data. Gathered data then analysed using SEM-PLS alogarithm. The unique result of this study shows that perceived income do not have significant effect on the use of digital payment to pay ZIS. The other variables from UTAUT show that performance expectancy and effort expectancy have a positive and significant influence on the use of digital payments in paying ZIS, while social influence and facilitating conditions do not significantly influence the use of digital payments in paying ZIS. These results suggest that BAZ of LAZ can enhance performance and effort expectancy in its payment application to be more engaged to customers, and making them continue to use digital payment to pay ZIS.